Metabolic Memory in Diabetes - Mechanistic Insights and the Impact of Cardiovascular Medication - Raluca SOSDEAN; Loredana N. IONICA; Adrian P. MERCE; Danina M. MUNTEAN; Adrian STURZA (Sciendo, 2021)
The prevalence of diabetes mellitus is increasing worldwide. Endothelial dysfunction plays a critical role in the pathophysiology of diabetes-related vascular complications. Several studies have shown that restoring blood glucose levels failed to reduce the incidence of major cardiovascular events in diabetic population, hence confirming the idea of "metabolic/hyperglycemic memory". The major pathomechanism is, most likely, represented by the overproduction of reactive oxygen species (ROS). The purpose of this minireview is to summarize current knowledge about the mechanisms of metabolic memory and the impact of cardiovascular medication on this phenomenon, respectively.